2002
DOI: 10.1073/pnas.182429899
|View full text |Cite
|
Sign up to set email alerts
|

Topical applications of caffeine or (−)-epigallocatechin gallate (EGCG) inhibit carcinogenesis and selectively increase apoptosis in UVB-induced skin tumors in mice

Abstract: SKH-1 hairless mice were irradiated with ultraviolet B (UVB) twice weekly for 20 weeks. These tumor-free mice, which had a high risk of developing skin tumors during the next several months, were then treated topically with caffeine (6.2 mol) or (؊)-epigallocatechin gallate (EGCG; 6.5 mol) once a day 5 days a week for 18 weeks in the absence of further treatment with UVB. Topical applications of caffeine to these mice decreased the number of nonmalignant and malignant skin tumors per mouse by 44% and 72%, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
217
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(226 citation statements)
references
References 35 publications
4
217
1
4
Order By: Relevance
“…When tea polyphenols are administered orally, their low bioavailability in the skin may limit the inhibitory effect; the contribution of caffeine present in tea to inhibiting carcinogenesis could become more important. Topical application of EGCG and caffeine to the skin was shown to decrease, by a similar extent, the incidence, multiplicity, and size of tumors induced by UVB treatment in SKH-1 mice [38,39].…”
Section: Skin Carcinogenesismentioning
confidence: 83%
“…When tea polyphenols are administered orally, their low bioavailability in the skin may limit the inhibitory effect; the contribution of caffeine present in tea to inhibiting carcinogenesis could become more important. Topical application of EGCG and caffeine to the skin was shown to decrease, by a similar extent, the incidence, multiplicity, and size of tumors induced by UVB treatment in SKH-1 mice [38,39].…”
Section: Skin Carcinogenesismentioning
confidence: 83%
“…52 Accordingly, pre-exposure of SKH-1 hairless mice to caffeine resulted in an enhanced rate of UVB-induced apoptosis in the epidermis 53 and protected the animals against photocarcinogenesis. 54 In addition, epidemiological data imply that daily caffeinated coffee consumption decreases the incidence and prevalence of NMSC in Caucasians, 55,56 indicating that CHK1 inhibition is indeed effective in terms of cancer chemoprevention in humans. As overexpression of CHK1 attenuated the enhanced apoptosis rate of UVB-exposed NCTC-shAHR KC, it is highly likely that the loss of checkpoint control drives damaged KC into the suicide program ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…EGCG exerts an inhibitory effect in many cancers, such as prostate cancer [20,21] and liver cancer [22] . Previous studies have shown that EGCG decreased the expression of COX-2 [23] and mPGES [15] .…”
Section: Discussionmentioning
confidence: 99%